(untitled) (Journal of the College of Basic Education, 2026)
There are many manifestations of semantic opposition in poetry it’s a rich system of semantic opposition that are described as opposing dualities that formed an effective expressive system in the poets expressive system . presence and absence constitute two focal points as they contain high enlightening energy that illuminates the text and expressive momentum because they represent an advanced state of coding it contains an encrypted semantic depth , as the deep elements of text work very effectively to direct the text and more it’s internal elements .